2017
DOI: 10.14689/ejer.2017.69.12
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and Explanatory Relationship Model between Procrastination, Motivation, Anxiety and Academic Achievement

Abstract: The purpose of this study is to determine the predictive and explanatory relationship model between procrastination, motivation, anxiety and academic achievement of university students. Research Methods: In this study, a causal research design was used. The study group consisted of 211 participants. In order to determine their motivation levels, Academic Motivation Scale (AMS); their anxiety levels, Foreign Language Classroom Anxiety Scale (FLCAS) and their procrastination levels, Aitken

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 42 publications
(58 reference statements)
6
19
0
7
Order By: Relevance
“…It is noted that the relationship between the need for cognition and trait emotional intelligence was statistically significant whereas the relationship between the need for cognition and academic achievement was not significant. This result supported the earlier findings on the relationship between need for cognition and academic success (Neigel et al, 2017) and contradicted the study findings that there is a significant relationship between students' levels of need for cognition and their academic achievement (Akpur, 2017;Luong et al, 2017;Richardson et al, 2012;von Stumm & Ackerman, 2013). According to Elias and Loomis (2002), the contribution of need for cognition to academic achievement lends credence to the belief that if students enjoy and seek out academic tasks, it should be reflected in their academic performance.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…It is noted that the relationship between the need for cognition and trait emotional intelligence was statistically significant whereas the relationship between the need for cognition and academic achievement was not significant. This result supported the earlier findings on the relationship between need for cognition and academic success (Neigel et al, 2017) and contradicted the study findings that there is a significant relationship between students' levels of need for cognition and their academic achievement (Akpur, 2017;Luong et al, 2017;Richardson et al, 2012;von Stumm & Ackerman, 2013). According to Elias and Loomis (2002), the contribution of need for cognition to academic achievement lends credence to the belief that if students enjoy and seek out academic tasks, it should be reflected in their academic performance.…”
Section: Discussionsupporting
confidence: 65%
“…Concerning previous research studies carried out in the area of need for cognition, it showed a significantly high positive relationship (Akpur, 2017;Elias & Loomis, 2002) , whereas some meta-analyses study results identified weak to moderate (Richardson, Abraham, & Bond, 2012;von Stumm & Ackerman, 2013) relationship between the need for cognition and the academic achievement of students. Parker, Creque, et al (2004) investigated the relationship between emotional intelligence and academic achievement among high school students in Huntsville, Alabama.…”
Section: Studies Related To Need For Cognitionmentioning
confidence: 83%
“…Akademik erteleme eğilimi olan öğrenciler, sınavlara hazırlanmamak, dönem ödevini yapmamak, haftalık okuma ödevlerini yerine getirmemek gibi yaygın ve benzer davranışlar sergilemektedirler (Onwuegbuzie & Jiao, 2000). Ayrıca akademik ertelemenin, sınav kaygısı ve düşük akademik başarı ile ilişkili olduğu belirtilmektedir (Balkıs, 2011;Hen & Goroshit, 2014).…”
Section: Introductionunclassified
“…Motivasyon öğrenci davranışlarının yönünü, şiddetini ve kararlılığını belirleyen en önemli faktörlerden biridir (Keller ve Kopp, 1987). Literatürde öğrencilerin motive olduklarında başarma çabalarının ve başarı düzeylerinin arttığına ilişkin çalışmalar bulunmaktadır (Akpur, 2017;Eccles, Wigfield ve Schiefele, 1998;Keller, 2010;Kutlu ve Sözbilir, 2011;Merlin, 2003). Dick, Carey ve Carey'ye (2005) göre öğrencilerin motivasyonlarının düşük olması durumunda öğrenmenin istenen düzeyde geçekleşmesi mümkün değildir.…”
Section: Introductionunclassified